Novel clonality assays for T cell lymphoma in cats targeting the T cell receptor beta, T cell receptor delta, and T cell receptor gamma loci. (20th December 2021) - Radtanakatikanon, Araya; Moore, Peter F.; Keller, Stefan M.; Vernau, William
Abstract: Background: T cell clonality assays in veterinary medicine currently target only the T cell receptor gamma (TRG) locus. Existing assays have suboptimal sensitivity because of insufficient primer coverage of all possible rearrangements. Objective: Develop higher sensitivity clonality assays targeting the TRG, delta (TRD), and beta (TRB) loci in cats. Animals: Cats with histopathologically confirmed lymphoma (n = 89), non‐lymphoma (n = 35), and possible hepatic small cell lymphoma (n = 31). Methods: Molecular clonality assay development utilizing our recently reported topology and expressed repertoire data of the T cell receptor loci in cats. Determination of clonality status of lymphoma, non lymphoma, and possible hepatic small cell lymphoma samples, and calculation of assay sensitivity and specificity. Results: The new multiplex TRG assay yielded the highest sensitivity (95.5%). All assays yielded 100% specificity except for the new multiplex TRG assay (97.3%). The combination of the new TRG and TRB assays yielded sensitivity of 98.9% and specificity of 97.0%. The new TRG assay detected clonality in 17/31 possible small cell lymphoma livers, whereas an existing TRG assay detected clonality in 6/31 livers. Conclusions and Clinical Importance: The assessment of multiple T cell loci compensates for the potential shortcomings of individual assays. Using a combination of molecular clonality assays will increase the overall sensitivity for the diagnosis of T‐cell lymphoma in cats, especially intestinal, and hepatic small cell lymphoma. Hepatic small cell lymphomas detected by the new TRG assay utilized rarely expressed V and J genes not recognized by previous assays, likely indicating unique biology of hepatic small cell lymphoma in cats.